Uma proposta de ensino de Mecânica Ondulatória e Acústica na formação universitária empregando TIC - Carvalho, Marcio Luciano Costa de (2018)
This research has been carried out in the first academic term in 2017 with a 6th-semester Mathematics students in Santa Maria Federal University. The studied comprised 29 subjects with an age average of 25 years. In this work, we intend to offer an alternative path for teaching and learning wave mechanics and acoustic in university formation using novel technological resources. The purpose is to supply contributions to the processes of higher education to augment the practices of different learning alternatives in a way that it can serve as a framework of contextualized activities for phases of classroom teaching. The present research can be framed within the qualititative action research based on Vigotsky theory applied to teaching. In this way, it is intended to give means for the student learning by employing social interactions generated by the students and mediated by the lecturer and that the learners have the possibilty to grasp meanings of physical concepts shared by the academic community and their representations through mathematical interpretation of signs and, in this way, promoting the rebuilding of internal concepts and sharing of them. Therefore, this work can refer to activities which aim to favour the acquisition of new knowledge relating the theory studied in lectures with the application of concepts in experimental tasks and using ICT (Information and Communication Technologies) and computer programming languages for modelling. Through careful observation of student classroom work and interests, questionnaires and analysis of Python computer codes and also the graded from written examination papers, we have obtained promising results that the teaching proposal shown in this work contribute to the processes of student knowledge retention. Following this, we highlight the collaboration of this approach in building up the critical posture of students during the learning and teaching processes.